2023
DOI: 10.3390/cancers15123230
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Global Research on Tumor Dormancy

Abstract: Tumor dormancy continues to be a research hotspot with numerous pressing problems that need to be solved. The goal of this study is to perform a bibliometric analysis of pertinent articles published in the twenty-first century. We concentrate on significant keywords, nations, authors, affiliations, journals, and literature in the field of tumor dormancy, which will help researchers to review the results that have been achieved and better understand the directions of future research. We retrieved research artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Notably, since core authors had published 78.31% of the total publications, it appears that the core author group is stable and plays an essential role in this domain. Additionally, the authors with the most publications were identified; Leucht Stefan (from Germany) was the most productive author, suggesting that these productive authors have made outstanding contributions to the field, and their future in-depth research is expected to provide the latest information in this field (Zhao et al, 2022 ; Zhang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, since core authors had published 78.31% of the total publications, it appears that the core author group is stable and plays an essential role in this domain. Additionally, the authors with the most publications were identified; Leucht Stefan (from Germany) was the most productive author, suggesting that these productive authors have made outstanding contributions to the field, and their future in-depth research is expected to provide the latest information in this field (Zhao et al, 2022 ; Zhang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis, only scienti c research collaborations between institutions with 6 or more publications were considered, and 60 of the 1221 institutions were ultimately included in the network analysis. The University of Pittsburgh stands out with the highest number of documents (31), followed closely by Stanford University (22), the University of Oxford (19), the University of Pennsylvania (19), and Duke University (16) (Fig. 3A).…”
Section: Analysis Of Authors Institutions and Countries/regionsmentioning
confidence: 99%
“…Our aim is to conduct a bibliometric analysis using Citespace (6.1.R6), VOSviewer (1.6. 19), and Scimago Graphica (1.0.35) to provide a scienti c reference for scholars [22][23][24] . Through the evaluation of existing data, our goal is to assist researchers in identifying detailed research topics, global research trends, and hot spots within the eld of the comorbidity between depression and insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, scientometric analysis conveniently provides an understanding of the development and frontiers of a particular research field for new researchers. Scientometric analysis has been applied widely in a variety of medical fields, such as psychiatry ( 11 , 12 ), oncology ( 13 ), infectious diseases ( 14 ), nursing ( 15 ), and neurology ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%